Design and Construction of a Free Energy Generator. - Tumwebaze, Edwine (Kabale University, 2024)
The main tittle of this project is design and construction a free energy generator where the main objective is to determine whether the concept of a free energy generator can be used to generate electricity without using other sources of energy like hydroelectric power, fossil fuel among others but using the natural properties of magnets (attraction and repulsion of the magnetic poles) to create a perpetual motion which can be used to perform a useful function. The permanent magnets have invisible and continuous power where it can attract the iron or other specific kind of metal with the energy flow which allows the permanent magnet to defy the gravity for years. Therefore, it is believed that the free energy can be extracted from the permanent magnets by arranging them in a special configuration.